METHOD OF ESTIMATION NATIONAL SECURITY IN AIR SPACE USE MANAGEMENT - A. M. Baranovskiy; O. A. Tyurin (Научный вестник МГТУ ГА, 2016)
The article presents the method of estimation of national security in air space use management, considering safety, economic and regularity of air traffic with respect to defensive capacity.